Synthesis, Analytical and Antimicrobial Studies of Co(II) Complexes of Macrocyclic Ligands - Ambwani, Jitendra; Kulshreshtha, Hemant; Mittal, Vanadana (Asian Journal of Chemistry, 2016)
In present work, the authors describe the synthesis of two macrocyclic complexes of Co(II) with the composition [Co(L)](BF4)2 [L = (DPIDAH) = 2,6-diacetyl pyridine N,N'-iminodiacetic acid dihydrazone or (PCCIDAH) = pyridine-2,6-dicarbonyl dichloride N,N'-iminodiacetic acid dihydrazone]. The complexes were characterized by elemental analyses, molar conductance, infrared and electronic spectra. The biocidal properties of the compounds were also reported.